Effects of Epibiotic Diatoms on the Productivity of the Calanoid Copepod Acartia tonsa (Dana) in Intensive Aquaculture Systems - Pan, Yen-Ju; Wang, Wei-Lung; Hwang, Jiang-Shiou; Souissi, Sami (Frontiers in Marine Science, 2021)
We evaluated here the effects of the epibiotic diatom Tabularia sp. on the productivity of the calanoid copepod Acartia tonsa (Dana) for assessing their risk on copepod intensive aquaculture industry for the provision of live feed. In the first experiment, uninfested and intensively infested females were cultivated individually for the assessment of egg production. Intensively infested females appeared to have a significantly lower egg production (5.0–9.0 eggs/female/d) than uninfested females (22.0–26.0 eggs/female/d) during 5 consecutive days. In the second experiment, effects of culture densities on diatom epibiosis were investigated in 9 L cultures at three different densities (200, 400, and 600 ind. L–1). Another culture at higher volume (250 L) and lowest density (200 ind. L–1) was also carried out to test the effect of culture volume on diatom epibiosis. The infestation rate (%), infestation intensity (ratio of surface diatom coverage levels, classified as levels 0–3) and daily egg harvest rate (number of harvested eggs per day per liter) were evaluated among the four culture populations. The copepods had higher infestation rate (53.69–60.14%) and intensity rate (high ratios at level 2 and 3) when the densities were increased from 200 ind./L to 400 and 600 ind./L. Although egg harvest increased with increasing culture density, it seemed that the diatom-infested A. tonsa population reach a saturated egg production when the density was higher than 400 ind./L. Nevertheless, the differences of culture volumes (250 and 9 L) appeared to be not to have any effect when the copepods were cultivated at the same density (200 ind./L). This study reveals for the first time that the epibiosis of the diatom Tabularia sp. reduces the individual egg production, and egg harvest rate in high-density culture of the copepod A. tonsa. Our findings implicate that diatom epibiosis should be avoid in copepod intensive culture systems.